Performance of Slash Pine (Pinus elliottii Engelm.) Vis-a-vis Chirpine (Pinus roxburghii Sargent) in Respect of Oleoresin Yield at Dehra Dun - Verma, V. P. S.; Pant, S. P. (Indian Forester, 1978)
The yield of oleoresin obtained from 38 year old trees of slashpine (Pinus elliottii Engelm.) planted at Dehradun is compared with that of the indigenous Chirpine (Pinus roxburghii Sargent) or almost the same age and comparable diameter and crown development. Both the species were tapped for 2 years (1975 and 1976) by the normal Indian method with weekly freshenings. Slashpine was found to yield 84.8 percent (with an error of Â± 8.8%) more resin than chirpine. It was observed that where as the average yield from chirpine was 1.901 kg the slashpine trees of almost the same age gave 3.516 kg of resin per season.